Recensione: GIOVANNI MARGINESU, Il costo del Partenone. Appalti e affari dell’arte greca, Salerno Editrice, 2020 (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
The essay of Giovanni Marginesu is a brand-new research on the economy of the ancient Greece. The author blends the history of art, the newest economic studies, the study on the inscriptions and the ancient writers. The book summarizes the history of ancient art, from the Archaic age to the fall of the Roman Empire. The focus is on Athens. The construction of the Acropolis in the age of Pericles is  exemplary and well-documented. The costs and the quotations of the erga of the sacred hill (Parthenon, Parthenos and Propylaia) are not bare data and numbers. Actually, the survey includes the backstage of the relations between the patrons and the artists; the relevance of the art market in the ancient world; the use of sacred and civic monies in the architectonical complexes, statues and paintings; the aftermath of the Roman conquest of Greece on the meaning and the value of the masterpieces.
Keywords: economy; Acropolis; Parthenon; Athens; Greece; art; market; cost